A Bitendinous Palmaris Longus: Aberrant Insertions and Its Clinical Impact - A Case Report - S. Iqbal; Raiz Iqbal; Faiz Iqbal (Journal of Clinical and Diagnostic Research, 2015)
Palmaris longus, phylogenetically a retrogressive muscle, exhibits significant anatomical variations compared to other muscles of the upper extremity. It is of great surgical importance because, it is the first option tendon for graft procedures in various cosmetic, plastic and reconstructive surgeries. It has also been widely used in various tendon transfer procedures in treating facial paralysis, ptosis correction, lip augmentation and digital pulley reconstruction. We report a rare variant pattern of Palmaris longus with duplicated tendons and with multiple insertions to thenar and hypothenar muscles, fasciae and the flexor retinaculum along with its normal continuation as palmar aponeurosis. Variations in its insertions not only contribute, but also augment the various pathological processes such as Dupuytren’s contracture, Carpal tunnel and Guyon’s syndromes. So it is of utmost importance for surgeons, physicians and radiologists, to be aware of these variations, well in advance.